Evaluation of Biofertilizer on Growth and Productivity of Solanum lycopersicum L. - Febrionny, Princessa Nandita; Azzahra, Annisa; Salsabila, Syarifah; Agustin, Niken; Tamalia, Aqilla Kalyca; Anjani, Ajeng Distya; Junairiah; Fatimah (Jurnal ILMU DASAR, 2025)
The increasing demand for tomatoes has prompted farmers to use chemical fertilizers, which can lead to soil degradation and reduced fertility. This study aims to determine the appropriate dose and frequency of biofertilizer application to enhance the growth and productivity of tomato plants (Solanum lycopersicum L.). The experiment was designed using a Completely Randomized Design (CRD) with 11 treatments, including both negative and positive controls. Three variations in biofertilizer doses were tested (5, 10, and 15 ml/plant), along with three different frequencies of application: once at one week after planting (1 WAP), twice (at 1 and 4 WAP), and three times (at 1, 4, and 8 WAP). Measured parameters included soil fertility (microbial population and functional microbial quality), plant growth (plant height, leaf count, stem diameter), and plant productivity (flower count). Quality of functional microbes were analyzed descriptively. Data of microbial population, plant growth and productivity were analyzed using Kruskal-Wallis and Mann-Whitney tests with a 5% significance level. The results showed significant differences in soil microbial populations and plant height between treatments, although no significant differences were observed in stem diameter, leaf number, or flower number. The treatment with 15 ml/plant applied three times (B15F3) exhibited the highest Relative Agronomic Efficiency (RAE) compared to other biofertilizer treatments (74.63%), but it was still lower than the control (chemical fertilizer). Therefore, higher doses and/or frequencies may be needed to further evaluate the effectiveness of the biofertilizer under test.